Effect of heat treatment on the antioxidant activities of two cultivars of sweet potatoes - H. M. S, Amir; Nahar K., Nurun; Iqba, Nida; F. R, Nur; Lee, L. H.; Firdhaus Mad Nordin, Mariam; M. S, Sharifudin; W. A K, Wan Rashidah; A. A. Mukred, Jameel; Zulkifli, Razauden Mohamed Ohamed; Zakaria, Mona Yap @ Mona (Penerbit Universiti Teknologi Malaysia, 2016)
Natural sources of antioxidants are derived from fruits, vegetables and wine, whilst artificial supplements are from teas and spices. Sweet potato (Ipomoea batatas) is an excellent natural source of vitamins and minerals, and likely a great source of antioxidant. The objective of this study is to analyze the antioxidant activity of orange sweet potato (Vitato) and purple sweet potato (All purple), prepared as heat dry and moist heat for 30 minutes at 100oC. All the samples were obtained from Pasir Puteh and MARDI Telong, Bachok, Kelantan, respectively. Both samples were soaked into methanol to obtain the crude extract prior to analyzing for antioxidant activity by using 2, 2-diphenyl-1-picryl hydrazyl (DPPH). IC50 values of dry heat and moist heat Vitato were 0.40mg/L and 0.20mg/L while dry heat and moist heat, All purple were 0.32mg/L and 0.19mg/L, respectively. Both moist heat samples enjoyed higher scavenging activities compared to dry heat samples. However, the All purple sample of moist heat is the most superior one. Significant difference of IC50 values between dry heat and moist heat sample differ significantly. Thus, this study clearly demonstrated that moist heat sweet potato exhibited excellent increase in antioxidant activity.